Uji Aktivitas Antijamur Bacillus siamensis C7B terhadap Jamur Colletotrichum scovillei Penyebab Penyakit Antraknosa pada Tanaman Cabai Besar (Capsicum annuum L.) - PARDIANTA PATRISIUS SINAGA; KHAMDAN KHALIMI; DEWA NGURAH SUPRAPTA (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2020)
Test of Antifungal Activity of Bacillus siamensis C7B Against Fungus Colletotrichum scovillei Causing Anthracnose Disease on Chili Pepper (Capsicum annuum L.) Colletotrichum scovillei is one of the species of fungi that causes anthracnose disease on chili peppers. The Purpose of this study was to determine the potential of B. siamensis C7B in inhibiting the growth of the fungus C. scovillei that causes anthracnose disease in large chili (C. annuum L.). This study was conducted in vitro by testing the antifungal activity of Bacillus siamensis C7B against three isolats of C. scovillei namely TBCR, SGCR, and GRCR on potato dextrose agar (PDA) and potato dextrose broth (PDB) media. The test results indicate that inhibition of the bacteria B. siamensis C7B able to inhibit the growth of fungi isolates of C. scovillei namely TBCR, SGCR, and GRCR with the percentage of inhibition respectively by 94,91%, 92,66%, and 91,47% when compared to the control on the observation of 21 days after inoculation. The inhibition test results of B. siamensis C7B filtrate at a concentration of 50% showed that the B. siamensis C7B filtrate was able to inhibit the growth of C. scovillei TBCR isolates with a percentage of inhibition activity of 90,27% when compared to control. The results of inhibition test of B. siamensis C7B on the formation of C. scovillei biomass of isolate TBCR showed that B. siamensis C7B was able to inhibit the formation of fungal biomass by 73,81% when compared to control. Further study is needed to evaluate the effectiveness of B. siamensis C7B to control anthracnose disease in vivo on chili pepper.